1998
DOI: 10.1080/09537109876618
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor, P-selectin and fibrinogen levels in patients with acute ischaemic and haemorrhagic stroke, and their relationship with stroke sub-type and functional outcome

Abstract: Although ischaemic stroke is associated with accentuated platelet function, it remains unclear whether this applies to all sub-types, especially lacunar infarcts, which differ from cortical infarction in their patho-aetiology. Similarly, conflicting evidence suggests that haemorrhagic stroke may, or may not, be associated with a hypothrombotic state. Levels of von Willebrand factor (vWF), fibrinogen, and P-selectin were measured within 48 h of ictus in 163 patients with acute ischaemic stroke and 40 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 23 publications
9
47
0
1
Order By: Relevance
“…Our findings of elevated blood markers of endothelial and platelet activation during the first 7 days after ischemic stroke are consistent with several previous studies that have examined E-selectin, [22][23][24] vWF, 25,26 and P-selectin 22 in acute stroke, but not with all studies. 27,28 Other studies involving smaller sample sizes have found that P-selectin is not increased in acute stroke 26 and that vWF remains elevated 3 months after stroke.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings of elevated blood markers of endothelial and platelet activation during the first 7 days after ischemic stroke are consistent with several previous studies that have examined E-selectin, [22][23][24] vWF, 25,26 and P-selectin 22 in acute stroke, but not with all studies. 27,28 Other studies involving smaller sample sizes have found that P-selectin is not increased in acute stroke 26 and that vWF remains elevated 3 months after stroke.…”
Section: Discussionsupporting
confidence: 81%
“…[22][23][24][25][26][27][28] The weaknesses of our study are that evidence of recent infection and information on use of medications (eg, aspirin, heparin, statins) were not sought among cases and controls, the diagnostic criteria used to distinguish etiological subtypes of ischemic stroke may not be valid or reliable, repeated blood measurements were not performed in the controls, follow-up of the cases was incomplete, and the reasons for incomplete follow-up of cases (eg, death, recurrent stroke, unwillingness) were not determined. We expected that Ϸ10% of our cases (who were hospitalized, had survived a few days after stroke, and were well enough to provide informed consent) may have died during the first 3 to 6 months, 29 and Ϸ5% may have experienced a recurrent stroke.…”
Section: Discussionmentioning
confidence: 99%
“…29 They also are found in patients with acute ischemic stroke 30 and were suggested to predispose to ischemic stroke. 31 This prompted us to investigate whether VWF plays an active role in ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Similarly, acute stroke is associated with low NOx and high vWf levels. 18,40 Although our trials were small, we used a crossover design (thereby allowing each subject to act as their own control) which considerably increases statistical power as compared with a parallel group design. Additionally, we assessed the effects of antiplatelet agents in two different sets of subjects which increases the validity of the findings.…”
Section: Discussionmentioning
confidence: 99%